ANALISIS PENGARUH DUKUNGAN ATASAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PARAMEDIS PUSKESMAS EKS KAWEDANAN LASEM, KABUPATEN REMBANG DENGAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI - 11.42.02.0059, Maryatin (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to analyze the influence of supervisor support and job characteristics on the performance of an employee health center Eks Kawedanan Lasem, Kabupaten Rembang with organizational commitment as mediation. Here is the entire population at the clinic former paramedic Eks Kawedanan Lasem, Kabupaten Rembang. Sampling was done by purposive sampling technique. Purposive sampling technique that is not based on the sampling strata, random, or a region but is based on a specific destination using the criteria. Criteria respondents is as follows: Employees with a minimum educational background D3 with a minimum tenure of 3 years. Mechanical testing data used in this study include test validity with factor analysis, reliability test by Cronbach alpha formula, multiple regression analysis, F test and the test of significance, test the mediating effect to validate the research hypothesis.Research shows that the ability of the model to correctly describe relations supervisor support variables, job characteristics and organizational commitment influence the employees performance.Key words : supervisor support, job characteristics, organizational commitment and employees performance